Financial Reporting Fraud in Indonesian Regional Banks: A Fraud Hexagon Analysis with Audit Committee Moderation - Widya Ais Sahla; Dwianto Mukhtar Latif; Muhammad Bahit (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the influence of Fraud Hexagon elements on fraudulent financial reporting and investigates whether audit committee effectiveness moderates these relationships in Indonesian Regional Development Banks (BPDs). Using secondary data from all 27 Indonesian BPDs over the 2016-2025 period, the study analyzes 270 firm-year observations. Fraudulent financial reporting is measured using the Beneish M-Score, and hypotheses are tested using Moderated Regression Analysis (MRA) with Pooled Ordinary Least Squares and robust standard errors. The findings reveal that financial targets (ROA), opportunity represented by receivable growth (RGW), and arrogance measured by CEO photo frequency (PIC) significantly increase fraudulent financial reporting. Conversely, financial stability, external pressure, capability, rationalization, and collusion are not significant predictors. Audit committee effectiveness exhibits limited moderating influence, significantly interacting only with opportunity and rationalization while failing to moderate the remaining Fraud Hexagon dimensions. This study extends Fraud Hexagon literature by examining the rarely investigated context of state-owned regional banks and incorporating audit committee effectiveness as a moderating mechanism. The findings suggest that regulators and bank management should prioritize governance quality through strengthening audit committee competence, independence, and substantive oversight rather than focusing solely on committee size. The study enriches Fraud Hexagon Theory and agency theory by demonstrating that the determinants of fraudulent financial reporting and the effectiveness of audit committee oversight are context-dependent in government-owned banking institutions.